JURIDICAL ANALYSIS OF THE RELEVANCE OF GOVERNMENT REGULATION NUMBER 80 OF 2019 CONCERNING E-COMMERCE WITH LAW NUMBER 7 OF 2014 CONCERNING TRADE - Erlina B; Dahlan Dahlan (Law Faculty of Universitas Bandar Lampung, 2022)
This journal discusses the relevance of government regulation number 80 of 2019 regarding e-commerce with law number 7 of 2014 concerning trade. The research method used is a normative and empirical juridical approach, using primary and secondary data obtained from literature studies. The results of the study show that government regulation number 80 of 2019 regarding e-commerce is relevant to law number 7 of 2014 concerning trade. because there are no conflicting norms in it. regulate more specifically regarding parties implementing, requirements, implementation, obligations of business actors, advertisements, offers, receipts, confirmations, contracts, payments, delivery of goods, exchange of goods in trade with electronic systems, protection of personal data